Crusted Scabies in Poorly Managed HIV Infected Patient at Tanga Regional Referral Hospital, Tanzania (Tanzania Medical Journal, 2023)
Severe immune suppression especially due to human immunodeficiency virus (HIV) infection, is a risk factor for crusted scabies. We report a case of 33-year-old man with poorly managed HIV infection who presented with four months’ history of scaly itching skin rashes which initially started on the wrist, elbow, buttocks, finger and toes webs, and thigh and later progressed to involve the whole body. As time went by the scales thickened and due to scratching led to mild bleeding over the skin and became infected with bacteria.Physical examination revealed generalized hyperkeratotic whitish brownish scales with excoriations, yellowish crusts indicating bacterial superinfection. Skin scrapings soaked in 10% of potassium hydroxide preparation examined under microscope revealed scabies mites. The patient was treated with oral ivermectin 12mg on day one then repeated on day 7 and 14 together with lindane lotion 1% applied at night on day 1, 7 and 14. He performed daily soaking with wet gauze of 0.1% potassium permanganate solution to treat local bacterial infection and application of vaseline petroleum gel mixed with glycerin. He was discharged on day 18th in very good condition after sessions of adherence counselling and restarted on antiretroviral drugs (ARVs).